2003
DOI: 10.1080/0265673021000017154
|View full text |Cite
|
Sign up to set email alerts
|

Sequential pathological and immunologic analysis of percutaneous microwave coagulation therapy of hepatocellular carcinoma

Abstract: For inoperable HCC patients, PMCT is one of the treatment choices shown to be effective. Apart from its tissue coagulation effect, an increased systemic immune response directed against the tumour may also play an important role in improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 12 publications
3
49
0
1
Order By: Relevance
“…Based on our clinical experience accumulated over 12 years, we determined that microwave ablation for secondary splenomegaly and hypersplenism is safe and effective. Previous studies have shown that immune function was enhanced in HCC patients receiving microwave ablation therapy for tumours [23][24][25][26][27]. However, changes in immune status of patients receiving microwave ablation for the spleen remained unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our clinical experience accumulated over 12 years, we determined that microwave ablation for secondary splenomegaly and hypersplenism is safe and effective. Previous studies have shown that immune function was enhanced in HCC patients receiving microwave ablation therapy for tumours [23][24][25][26][27]. However, changes in immune status of patients receiving microwave ablation for the spleen remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…PMCT can produce a controlled volume of necrosis and can be used for haemostasis, so it might be adopted to decrease the splenic parenchyma in treating hypersplenism. It was reported that in patients receiving microwave ablation therapy for HCC, the immune function towards tumour was enhanced [23][24][25][26][27]. However, no studies have been conducted yet studying the effects of microwave ablation therapy for splenomegaly and hypersplenism on parameters associated with the patient's immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Third, as the tumor recurrence rate is high even after complete tumor ablation, adjuvant therapies may be employed after MWA to inhibit tumor relapse, and further studies are warranted to observe the effectiveness of adjuvant therapies. Improvement of the patient’s immune status is beneficial to long-term survival [59]. Immunologic therapy may be adopted in the future to up-regulate the systemic immune response towards tumor.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…The results of our previous research demonstrated that PMWA stimulated local immune response, however lasting only a short time, suggesting that immunotherapy after ablation therapy should be performed. 16 Tumor load is temporarily reduced to a minimum after ablation therapy of HCC, which represents the best opportunity to perform immunotherapy. Therefore, we planned two courses of adoptive immunotherapy with multiple immunocytes and multiple reinfusion routes to be undertaken within 11 days post-PMWA, and one additional course to be started 100 days after PMWA.…”
Section: Discussionmentioning
confidence: 99%